The Impact of Primary Progressive Aphasia on Picture Naming and General Language Ability. Issue 3 (September 2021) - Peristeri, Eleni; Messinis, Lambros; Kosmidis, Mary H.; Nasios, Grigorios; Mentis, Alexios-Fotios A.; Siokas, Vasileios; Aloizou, Athina-Maria; Kotrotsios, Anastasios; Andreou, Maria; Dardiotis, Efthimios
Abstract : Background: Primary progressive aphasia (PPA) is a clinical syndrome that is characterized by progressive deterioration of language while other cognitive domains remain relatively intact. The extent to which print exposure and cortical volume atrophy jointly influence picture naming and general language ability in individuals with PPA remains underexplored. Objective: To investigate the language performance of individuals with the nonfluent variant of primary progressive aphasia (nfvPPA) and to explore the impact of print exposure and cortical volume atrophy on their language ability. Method: We compared 14 Greek individuals with nfvPPA and similar age, education, disease duration, and cognitive ability with age-, gender- and education-matched Greek controls on picture naming and on language tasks of the Boston Diagnostic Aphasia Examination—Short Form, including oral word reading, word and sentence repetition, complex ideational material, and reading comprehension. The effects of print exposure and left-hemisphere cortical volume on the individuals' language performance were estimated through stepwise regression models. Results: The language performance of the individuals with nfvPPA was affected by print exposure and cortical volume atrophy. Picture naming and word reading were affected by print exposure. The highest contributions of cortical volume atrophy were found for the repetition, complex ideational material, and reading comprehension tasks. Conclusion: Print exposure and cortical volume atrophy may help explain variability in the language performance of nfvPPA individuals with similar age, education, disease duration, and cognitive ability. Abstract : Supplemental Digital Content is available in the text.